Poética fílmica: o exemplo de Alfred Hitchcock - Santos, Marcelo Moreira (2012)
This thesis had the objective of studying Poetics of Film. Considering poetry, in the case of cinema, as the process of creation, production and effect achieved by the film, this research s question was: how is a systemic semiotic unit created in a film? Its goal, therefore, was to understand how poetics is structured and engendered. The hypothesis that guided this research were the following: 1) the signs characteristics, which are the hybrid language of cinema, are formed by the integration and complementation of semiotic principles and developments of the aural, visual and verbal languages, 2) the film s systemic ontology is characterized by a collaborative authorship and a complex process of semiosis and communication. To achieve its objective, the research was based on the junction of the Peircean semiotic theory and Edgar Morin and Jorge Vieira s theory of systems. This junction allowed the understanding of the hybrid nature of the filmic sign, which is based on the intersection of three semiotic principles developed by Santaella: syntax, form and discourse. Thus, the filmic interpretation was carried out from Peirce's theory of the interpretants, along with systemic evolutionary parameters. Considering that the cinematography of Alfred Hitchcock constitutes a unique case of an optimized entanglement between semiotics and systemics, the research focused on the study of carefully selected parts from three films by the director: Rear Window (1954), Vertigo (1958) and Psycho (1960). The choice is due to the fact that this filmmaker prepares exemplarily a complex unity in his films, working the characteristics of each language - visual, aural and verbal - on both its autonomy and on the interfaces and integrations between them, generating poetics, ie a way of internal engendering that organizes different elements in a systemic dynamics. The analysis revealed that the suspense in Hitchcock is based on the geometrization of a network of intersemiosis that flows, uniting itself by attractive structures, through which timelines of events and information gradually reveal a representative grammaticality. Thus, in addition to situate and contextualize Hitchcock in poetics of film articulated in different schools and movements throughout history, this research established the concept of systemic ontology cinematography. For, in its ontological bias, the poetics of film is made by an organization of diverse and plural nature, whose active unit is established and maintained by the multiplicity of interactions and cooperation which the semiotics agents involved, with their specialties and functions, are able to produce, develop and transform